2010
DOI: 10.1007/978-3-642-12607-9_28
|View full text |Cite
|
Sign up to set email alerts
|

Designing Mobility: Pervasiveness as the Enchanting Tool of Mobility

Abstract: PLUG -Play Ubiquitous Games -, is a research project that deployed a fully distributed RFID architecture in the Museum of Arts and Crafts in Paris. A pervasive game was designed: "Plug: the Secrets of the Museum" (PSM) where players had to find virtual representations of the Museum artifacts, scatter them around or tidy them in the right spots, or swap them with other players. The analysis of the players' feed back showed that three main features characterize mobility when it is connected to pervasiveness. Fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…The analysis of the players' feed back showed that three main features characterize mobility when it is connected to pervasiveness [2]. First, mobility appears as a way to read and collect information.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the players' feed back showed that three main features characterize mobility when it is connected to pervasiveness [2]. First, mobility appears as a way to read and collect information.…”
Section: Resultsmentioning
confidence: 99%
“…Though Korean Gangneung Danoje Festival is similar to Chinese Dragon Boat Festival and the festival is of certain possibility being transmitted from China at the earliest, Korean Gangneung Danoje Festival is considered as the festival of Gangneung people actually if we analyze in the aspect of celebration ceremony. Gangneung people regard the mythological figures who they believe in as the sacrificing objects; moreover, the etiquette of the sacrifice has distinct local features of Gangneung; scenery and entertainment in the festival, especially, can reflect the cultural deposits of Gangneung people which have been inherited for generations [14][15][16].…”
Section: The Gangneung Danoje Festivalmentioning
confidence: 99%